Tinea Capitis among Elementary School Students in Jatinangor,Sumedang, West Java - Aprilia, Dilla; Ramali, Lies Marlysa; Sadeli, Ramlan (Althea Medical Journal, 2016)
Background: Fungal infection is a common disease in tropical and subtropical countries. Warm and humid climates provide a favourable environment for organism causing superficial mycosis. One of the fungal infections that commonly occurred in children is tinea capitis. Tinea capitis is a superficial fungal infection of the hair and scalp caused by dermatophytes. The age predilection of this disease is children aged 3 until 14 years . The purpose of this study was to detect the presence of tinea capitis among elementary school students in Jatinangor, Sumedang, Indonesia.Methods: This cross-sectional descriptive study involved 391 students from thefirst until sixth grade at four elementary schools in Jatinangor, in the period of September until October 2013. Anamnesis, physical examination, Woodâs lamp examination and direct microscopic examination were conducted to diagnose the disease. The collected data were analyzed and presented in the form of frequency distribution and percentages shown in tables.Results: Out of 391 students participating in this study, 194 were boys and 197 were girls. The age range was 6 until 16 years. Based on the screening results, 74 students were known to have complaints about their hair and scalp and only 49 students could continue the study as they have no positive result of tinea capitis.Conclusions: There is no positive findings of tinea capitis according to anamnesis, physical examination, Woodâs lamp examination and direct microscopic examination. Further examination by culture with Sabouraudâs dextrose agar should be carried out. [AMJ.2016;3(3):340â4]Â DOI: 10.15850/amj.v3n3.876